The Hidden Value of Adult Informal Care in Europe - Joan Costa-Font; Cristina Vilaplana-Prieto (Institute of Labor Economics (IZA), 2024)
The hidden value of adult informal care (IC) refers to the unaccounted value of informal care in overall costs of long-term care (LTC) estimates. This paper estimates the net value of adult IC in Europe, drawing on a well-being-based methodology. We use an instrumental variable strategy and a longitudinal and cross-country dataset to estimate the causal effect of the extensive and intensive margin of caregiving on subjective well-being. Finally, we estimate the so-called compensating surplus (CS), namely the income equivalent transfer, to compensate for the net disutility of caregiving. IC reduces average subjective well-being by about 1% compared to the mean (6% among co-residential caregivers). Relative to a country's Gross Domestic Product (GDP), the value of informal care ranges between 4.2% in France and 0.85% in Germany. Such relative value is inversely correlated with the country's share of formal LTC spending, leading to reconsidering LTC regimes. The average CS per hour for IC is 9.55 exteuro, with a range from 22 exteuro per hour in Switzerland to 5 exteuro per hour in Spain. Additionally, long-term CS tends to be lower than short-term CS.
Keywords: I18; J17; J18; 330; caregiving; the value of time; wellbeing methods; Informal care; life satisfaction; daughters